A polishing pad material and its preparation method and application

CN119871213BActive Publication Date: 2026-10-27QUZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510118294.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2026-10-27
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

[0005]本发明的目的在于克服现有技术的不足,提供了一种抛光垫材料及其制备方法和应用,解决了现有的抛光垫材料研磨后硅片表面缺陷较多的技术问题

Benefits of technology

[0007]本发明主要是在凝固成型时利用适宜浓度的N,N-二甲基甲酰胺溶液来促进聚氨酯链的有序排列,浸渍布的适宜含水量可以确保聚氨酯的均匀凝固成型。本发明通过控制浸渍布的含水量和凝固成型时N,N-二甲基甲酰胺溶液的浓度,使得抛光垫材料可以形成较为稳定均一的微孔结构,以减少软质抛光垫材料抛光后的晶圆硅片的表面缺陷,解决了现有的抛光垫材料研磨后硅片表面缺陷较多的技术问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119871213B_ABST
    Figure CN119871213B_ABST
Patent Text Reader

Abstract

The present application relates to the field of chemical mechanical polishing processing, in particular to a kind of polishing pad material and its preparation method and application. Mainly in solidification forming, the ordered arrangement of polyurethane chain is promoted using suitable concentration of N,N-dimethylformamide solution, and the suitable water content of impregnated cloth can ensure the uniform solidification of polyurethane. By controlling the water content of impregnated cloth and the concentration of N,N-dimethylformamide solution during solidification, the polishing pad material can form a relatively stable and uniform microporous structure, to reduce the surface defects of wafer silicon after polishing of soft polishing pad material, and solve the technical problem of many surface defects of silicon wafer after polishing of existing polishing pad material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of chemical mechanical polishing, specifically to a polishing pad material, its preparation method, and its application. Background Technology

[0002] Chemical mechanical polishing (CMP) technology, with its unique material removal capabilities and surface treatment precision, not only occupies a core position in semiconductor integrated circuit manufacturing, but also demonstrates broad application potential and value in fields such as advanced materials processing.

[0003] Polishing heads, polishing pads, and polishing slurries are the core elements required for chemical mechanical polishing (CMP) processing and have a significant impact on the technology. As semiconductor device sizes continue to shrink and structural complexity increases, the requirements for surface defects in polished silicon wafers used in semiconductor devices are becoming increasingly stringent. Especially in advanced node integrated circuit manufacturing, even minute surface defects can lead to chip performance degradation or even failure.

[0004] Polishing pads can be classified into two categories based on hardness: hard pads and soft pads. Hard polishing pads are generally made of materials such as porous alumina or silicon nitride, while soft polishing pads are generally made of elastic materials such as polyurethane or polyetheretherketone. In particular, silicon wafers polished using existing soft polishing pad materials often exhibit numerous surface defects, making it difficult to meet the requirements of semiconductor integrated circuit manufacturing. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a polishing pad material, its preparation method and application, which solves the technical problem of many defects on the surface of silicon wafers after polishing with existing polishing pad materials.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides a method for preparing a polishing pad material, comprising the following steps: The impregnated cloth is soaked in water to obtain a base material with a moisture content between 25 wt% and 28 wt%. A polyurethane slurry is uniformly coated on the surface of the base material and solidified in an N,N-dimethylformamide solution to obtain an intermediate. The intermediate is washed, dried, and surface-treated to obtain a polishing pad material. The concentration of the N,N-dimethylformamide solution is 12 wt% to 17 wt%.

[0007] This invention primarily utilizes an appropriate concentration of N,N-dimethylformamide solution during solidification to promote the orderly arrangement of polyurethane chains. The suitable moisture content of the impregnated cloth ensures uniform solidification of the polyurethane. By controlling the moisture content of the impregnated cloth and the concentration of the N,N-dimethylformamide solution during solidification, this invention enables the polishing pad material to form a more stable and uniform microporous structure. This reduces surface defects on silicon wafers polished with soft polishing pads, solving the technical problem of numerous surface defects on silicon wafers after polishing with existing polishing pad materials.

[0008] Optionally, the coating thickness of the polyurethane slurry is 1.5 mm to 2.0 mm.

[0009] Optionally, the solidification process includes the following steps: A base coated with polyurethane slurry is immersed at a certain angle into an N,N-dimethylformamide solution until it is completely submerged. Let α be the angle formed between the plane of the polyurethane-coated base and the surface of the N,N-dimethylformamide solution, where α is between 25° and 35°. When α exceeds the range of 25° to 35°, the solidification effect of the polyurethane slurry will be affected, and water-filled cavities may even form in the solidified polyurethane coating.

[0010] Preferably, the polyurethane slurry exhibits the best solidification and molding effect when the value of α is 30°.

[0011] Optionally, the water washing process includes: after intermittent water washing 15 times, soaking in water for 5 to 15 minutes, and then intermittently washing 15 times again.

[0012] Optionally, the surface treatment includes sequentially performing a grinding process and a grooving process, wherein the grinding process is used to expose the porous structure of the polishing pad material, and the grooving process is used to form a surface groove structure on the surface of the polishing pad material.

[0013] This invention provides a polishing pad material, which is prepared using the above-described method.

[0014] This invention provides an application of the above-mentioned polishing pad material in chemical mechanical polishing.

[0015] Compared with existing technologies, the beneficial effects of this invention are as follows: This invention primarily utilizes an appropriate concentration of N,N-dimethylformamide solution during solidification to promote the orderly arrangement of polyurethane chains, and the appropriate moisture content of the impregnated cloth ensures uniform solidification of the polyurethane. By controlling the moisture content of the impregnated cloth and the concentration of the N,N-dimethylformamide solution during solidification, this invention enables the polishing pad material to form a relatively stable and uniform microporous structure, thereby reducing surface defects on the silicon wafer after polishing with soft polishing pad materials. This solves the technical problem of numerous surface defects on silicon wafers after polishing with existing polishing pad materials. Subsequent experimental results demonstrate that the polishing pad material prepared by the method provided in this invention can be successfully applied to chemical mechanical polishing (CMP). Attached Figure Description

[0016] Figure 1 The images provided by this invention are scanning electron microscope (SEM) images of the cross-sectional microporous structures of polishing pad materials with different water contents. Figures a) to e) are SEM images of the cross-sectional microporous structures of the polishing pad materials prepared in Comparative Example 1, Example 1, Example 2, Comparative Example 2, and Comparative Example 3, respectively.

[0017] Figure 2 The images provided by this invention are scanning electron microscope (SEM) images of the cross-sectional microporous structures of polishing pad materials prepared by solidification with N,N-dimethylformamide solutions of different concentrations. Figures a) to d) are SEM images of the cross-sectional microporous structures of the polishing pad materials prepared in Comparative Examples 4 to 7, respectively; Figures e) to g) are SEM images of the cross-sectional microporous structures of the polishing pad materials prepared in Examples 1, 3, and 4, respectively; and Figures h) to k) are SEM images of the cross-sectional microporous structures of the polishing pad materials prepared in Comparative Examples 8 to 11, respectively.

[0018] Figure 3 The images provided by this invention are scanning electron microscope (SEM) images of the cross-sectional microporous structures of polishing pad materials using polyurethane slurry with different coating thicknesses. Figures a) to c) are SEM images of the cross-sectional microporous structures of the polishing pad materials prepared in Examples 1, 5, and 12, respectively.

[0019] Figure 4 This diagram illustrates the distribution of sampling points for analyzing and testing the surface opening size of the polishing pad material provided by this invention.

[0020] Figure 5 A statistical diagram of the sampling point opening size of the polishing pad material A provided by the present invention.

[0021] Figure 6 A statistical diagram of the sampling point opening size of the polishing pad material B provided by the present invention.

[0022] Figure 7Scanning electron microscope (SEM) images of cross-sections of different polishing pad materials provided by the present invention. Specifically, a) is a microporous structure diagram of polishing pad material A', b) is a microporous structure diagram of polishing pad material A, and c) is a microporous structure diagram of polishing pad material B.

[0023] Figure 8 The present invention provides scanning electron microscope (SEM) images of the surfaces of different polishing pad materials and corresponding ImageJ software analysis images. In the figures, a) is an SEM image of the surface of polishing pad material A, b) is the ImageJ software analysis image corresponding to a) image, c) is an SEM image of the surface of polishing pad material B, and d) is the ImageJ software analysis image corresponding to c) image.

[0024] Figure 9 A statistical comparison chart of the number of pores per unit area for different polishing pad materials provided by this invention.

[0025] Figure 10 A statistical comparison chart of the pore areas of different polishing pad materials provided by this invention.

[0026] Figure 11 A statistical comparison chart of the porosity of different polishing pad materials provided by the present invention.

[0027] Figure 12 A comparative graph showing the correlation between the unevenness of different polishing pad materials provided by this invention and the oxide removal rate.

[0028] Figure 13 The diagrams show a comparison of defect distributions for different polishing pad materials provided by this invention. Figures a) to c) are defect diagrams corresponding to test condition 1 in Table 4; figures d) to f) are defect diagrams corresponding to test condition 2 in Table 4; and figures g) to i) are defect diagrams corresponding to test condition 3 in Table 4. Detailed Implementation

[0029] To address the aforementioned technical problems, this invention provides a polishing pad material, its preparation method, and its application. The technical solution and embodiments of this invention will now be described in detail with reference to the accompanying drawings.

[0030] This invention provides a method for preparing a polishing pad material, comprising the following steps: Preparation of coating slurry: Prepare the test coating slurry using a 1000ml graduated cylinder according to the test requirements. First, add a certain amount of N,N-dimethylformamide to the graduated cylinder and mix with pure water. Then, add a certain amount of polyurethane resin and colorant. Stir at 500 rpm for 20 minutes using a mixer, adjusting the rotor length during stirring to ensure uniform mixing. After stirring, place the coating slurry in a vacuum chamber for vacuum extraction until all bubbles disappear. Then, remove the slurry to be coated and seal the mouth of the graduated cylinder with plastic wrap.

[0031] Moisture content control: Cut a 15cm x 15cm piece of impregnated fabric with a knife, soak it in a pre-coagulation tank for 10 minutes, then remove it. Adjust the moisture content by adjusting the gap between the rolling mills, and measure the average moisture content of the front, middle, and rear sections using a moisture content meter. The impregnated fabric after this treatment is called a base.

[0032] Coating: Take out a glass plate and wipe it with a non-woven cloth dampened with alcohol. Secure the test base (after moisture content measurement) to the glass plate with tape. First, secure the top of the base, then the left side, smooth it out by hand, and then secure the right side, finally securing the bottom. When securing, adhere the tape to the edges of the base to leave ample area for coating. Place the glued glass plate on the large glass plate and secure the two plates together with tape. Place 2mm measuring tapes on both sides of the base. Pour 40ml of slurry horizontally and slide it evenly and parallel using a clean steel rod. Use a scraper to clean the slurry around the edges. Allow the coating to sit for 30 seconds before immersing in water.

[0033] Solidification and molding: Remove the measuring tape with a knife, and place the base coated with polyurethane slurry into a solidification tank containing N,N-dimethylformamide solution. Avoid impacting the sides of the tank. Solidification time is 30 minutes. Insert mercury into the solidification tank to measure the solidification temperature.

[0034] In this process, the plane containing the base coated with polyurethane slurry forms an angle of 30° with the surface of the N,N-dimethylformamide solution. The polyurethane slurry exhibits the best solidification and molding effect when the angle is 30°.

[0035] Washing: Remove the sample and wash it 15 times with controlled rolling mill intervals to avoid orange peel effect. After soaking in pure water for 10 minutes, wash it again 15 times with the rolling mill.

[0036] Drying: Place the sample on a pad, use clips to secure it around the edges to prevent warping, and dry it in a vacuum oven at 90°C for 30 minutes before removing it.

[0037] Surface finishing: The dense layer of the polyurethane film is ground away by a grinding wheel to expose the top of its finger-shaped holes.

[0038] Grooving: The texture is formed by hot pressing a heated embossing roller onto the surface of the film. Grooving can improve the uniformity of polishing pressure distribution on the polishing pad material, which is beneficial to improving processing quality.

[0039] The manufacturers and specifications of the main raw materials used in this invention are shown in Table 1: Table 1 Production Raw Material Information The present invention will now be described in detail through specific embodiments. These embodiments are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0040] Example 1 This embodiment provides a method for preparing a polishing pad material, specifically including the following steps: Step 1, Preparation of polyurethane slurry.

[0041] Prepare the test coating slurry using a 1000ml graduated cylinder according to the test requirements. First, add 127g of N,N-dimethylformamide to the graduated cylinder and mix with 22g of pure water. Then, add 438g of polyurethane resin, 22g of color powder, and a dispersant to form a color paste. The dispersant accounts for 0.5% of the mass of the polyurethane slurry. Stir the mixture for 20 minutes at 500 rpm using a mixer, adjusting the rotor length during stirring to ensure even mixing. After stirring, use a vacuum machine to evacuate the polyurethane slurry until all air bubbles disappear. Remove the polyurethane slurry and seal the mouth of the graduated cylinder with plastic wrap.

[0042] Step 2, preparation of the bass.

[0043] A 15cm×15cm impregnated fabric was soaked in a pre-coagulation tank filled with water for 10 minutes. After soaking, the fabric was removed and the moisture content was adjusted by the gap between the rolling mills to make the moisture content of the impregnated fabric 25wt%, thus producing a bass.

[0044] Step 3, preparation of intermediates.

[0045] Take out a glass plate and wipe it with a non-woven cloth dampened with alcohol. Secure the base to the glass plate with tape. When securing, stick the tape to the edge of the impregnating cloth to leave more area for coating. Place the glued glass plate on the large glass plate and secure the two glass plates together with tape. Place a 2mm measuring tape on each side of the impregnating cloth. Pour 40mL of polyurethane slurry horizontally and slide it evenly and parallel using a clean steel rod. Use a scraper to clean the slurry around the edges. Let the coating sit for 30 seconds before immersing in water.

[0046] Remove the measuring tape with a knife, place the base coated with polyurethane slurry into a coagulation tank containing N,N-dimethylformamide solution, and perform coagulation molding to obtain an intermediate.

[0047] The solidification time was 30 minutes, and the concentration of the N,N-dimethylformamide solution was 12%. When the base coated with polyurethane slurry entered the N,N-dimethylformamide solution, an angle of 30° was formed between the plane of the base coated with polyurethane slurry and the surface of the N,N-dimethylformamide solution. The coating thickness of the polyurethane slurry on the base was 1.5 mm.

[0048] Step 4, preparation of polishing pad material.

[0049] The intermediate is washed with water, dried and surface treated to obtain the polishing pad material.

[0050] The washing process includes: washing the intermediate material 15 times with a rolling mill, soaking it in pure water for 10 minutes, and then washing it 15 times again with a rolling mill to avoid orange peel effect. The drying process includes: placing the washed intermediate material in a vacuum oven at 90℃ for 30 minutes. The surface treatment includes grinding and grooving. Grinding involves using a grinding wheel to remove the dense polyurethane layer on the surface of the polishing pad material to expose the porous structure. Grooving involves using a heated embossing roller to hot-press textures onto the surface of the polishing pad material after grinding to form a surface groove structure.

[0051] Example 2 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the moisture content of the impregnated cloth in step 2 is 27 wt%.

[0052] Example 3 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 15%.

[0053] Example 4 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 17%.

[0054] Example 5 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the coating thickness of the polyurethane slurry on the base in step 3 is 2 mm.

[0055] Example 6 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the water content of the impregnated cloth in step 2 is 28 wt%, the concentration of the N,N-dimethylformamide solution in step 3 is 17%, and the coating thickness of the polyurethane slurry on the base in step 3 is 1.5 mm.

[0056] Comparative Example 1 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the moisture content of the impregnated cloth in step 2 is 22 wt%.

[0057] Comparative Example 2 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the moisture content of the impregnated cloth in step 2 is 30 wt%.

[0058] Comparative Example 3 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the moisture content of the impregnated cloth in step 2 is 35 wt%.

[0059] Comparative Example 4 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 0%, even if water is used instead of the N,N-dimethylformamide solution.

[0060] Comparative Example 5 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 3%.

[0061] Comparative Example 6 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 5%.

[0062] Comparative Example 7 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 8%.

[0063] Comparative Example 8 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 20%.

[0064] Comparative Example 9 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 23%.

[0065] Comparative Example 10 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 25%.

[0066] Comparative Example 11 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the concentration of the N,N-dimethylformamide solution in step 3 is 30%.

[0067] Comparative Example 12 This embodiment provides a method for preparing a polishing pad material, the specific steps of which are as follows: The preparation method is the same as in Example 1, except that the coating thickness of the polyurethane slurry on the base in step 3 is 2.5 mm.

[0068] Test 1: Scanning Electron Microscopy Test The micropore shape and size of the polishing pad material were studied using a scanning electron microscope. The polishing pad materials of Examples 1-5 and Comparative Examples 1-12 were vertically cut into surface and cross-sectional samples with a size of 10mm×10mm×5mm. The accelerating voltage of the scanning electron microscope was set to 15kV.

[0069] The preferred structure for polishing pad materials is a micropore shape that produces relatively regular "teardrop" or "finger-like" pores. This is because the finger-like structure is an excellent structure, which facilitates the storage of polishing fluid in the polishing pad and results in better polishing performance.

[0070] The results of the scanning electron microscopy test are as follows: Scanning electron microscope (SEM) images of the cross-sectional microporous structures of the polishing pad materials prepared in Examples 1-2 and Comparative Examples 1-3 are shown below. Figure 1 As shown, Figures a) to e) are scanning electron microscope (SEM) images of the cross-sectional micropore structures of the polishing pad materials prepared in Comparative Examples 1, 1, 2, 2, and 3, respectively. A comparison of the micropore shapes in Figures a) to e) shows that, compared to Comparative Examples 1-3, the micropore shapes of the polishing pad materials prepared in Examples 1-2 are closer to a "teardrop" shape.

[0071] When the moisture content of the impregnated fabric is relatively low, less than 25%, an equilibrium is formed between water and N,N-dimethylformamide, limiting the diffusion rate of the polyurethane resin solution. Water molecules gradually replace the N,N-dimethylformamide solvent in the slurry, but because the water content in the impregnated fabric is not excessive, the microphase separation is relatively uniform, and the resulting micropores are relatively small. However, when the moisture content of the impregnated fabric exceeds 28%, the number of water molecules increases, and the effect of water becomes more significant. This leads to water molecules forming larger and more irregular voids during polyurethane resin diffusion, resulting in coarser micropores. In summary, the preferred moisture content range for the impregnated fabric is 25wt% to 28wt%.

[0072] Scanning electron microscope (SEM) images of the cross-sectional micropore structures of the polishing pad materials prepared in Examples 1, 3, 4, and Comparative Examples 4–11 are shown below. Figure 2 As shown in the figures, figures a) to d) are scanning electron microscope (SEM) images of the cross-sectional micropore structure of the polishing pad materials prepared in Examples 4 to 7, respectively; figures e) to g) are SEM images of the cross-sectional micropore structure of the polishing pad materials prepared in Examples 1, 3, and 4, respectively; and figures h) to k) are SEM images of the cross-sectional micropore structure of the polishing pad materials prepared in Examples 8 to 11, respectively. A comparison of the micropore shapes in figures a) to k) shows that, compared to Examples 4 to 11, the micropore shapes of the polishing pad materials prepared in Examples 1, 3, and 4 are closer to a "teardrop" shape.

[0073] At N,N-dimethylformamide concentrations below 12%, the faster the bidirectional diffusion rate of N,N-dimethylformamide and water, the easier it is for a surface film to form, resulting in coarse micropore shapes. As the N,N-dimethylformamide concentration increases to 15%, interfacial pores gradually appear between the polyurethane layer and the substrate in the wet-coated film. This is because the increased N,N-dimethylformamide concentration generates significant stress at the interface, causing polyurethane nucleation and precipitation near the interface. When the N,N-dimethylformamide concentration reaches 17%, the concentration gradient of each substance decreases rapidly, improving the stability of the polyurethane in the inner layer mixture and forming a uniform and fine microporous structure. The region between the polyurethane layer and the substrate is called the dense layer. However, when the N,N-dimethylformamide concentration increases to a certain level, the higher the N,N-dimethylformamide concentration, the thicker the dense layer, hindering diffusion and preventing the effective formation of a uniform and fine microporous structure, resulting in irregular micropore morphology and even the appearance of bifacial pores. In summary, the preferred range for N,N-dimethylformamide is 12wt% to 17wt%.

[0074] Scanning electron microscope (SEM) images of the cross-sectional micropore structures of the polishing pad materials prepared in Examples 1, 5, and 12 are shown below. Figure 3As shown, Figures a) to c) are scanning electron microscope (SEM) images of the cross-sectional micropore structures of the polishing pad materials prepared in Examples 1, 5, and 12, respectively. A comparison of the micropore shapes in Figures a) to c) shows that, compared to Comparative Example 12, the micropore shapes of the polishing pad materials prepared in Examples 1 and 5 are closer to a "teardrop" shape.

[0075] Scanning electron microscopy (SEM) images reveal significant differences in the microporous structures, which is attributed to variations in solidification time. At a coating thickness of 1.5 mm, the solidification time is faster, resulting in more uniform interdiffusion and phase separation of N,N-dimethylformamide and water, leading to microporous structures that closely resemble water droplets. Conversely, at a thicker coating thickness of 2.5 mm, the solidification time is slower, resulting in uneven interdiffusion and phase separation of the solvent and water, causing the microporous structures to become noticeably larger and smaller.

[0076] The present invention employs the following tests to characterize the properties of polishing pad materials A, A', and B: A' is the type of polyurethane polishing pad prepared before this project's research, with the following preparation parameters: N,N-dimethylformamide concentration in the coagulation tank 15%, base material moisture content 25%, and coating thickness 1.5 mm. A is the preferred polyurethane polishing pad after the research, with the following preparation parameters: N,N-dimethylformamide concentration in the coagulation tank 17%, base material moisture content 28%, and coating thickness 1.5 mm. Detailed preparation steps are provided in Example 6. B is a polishing pad material provided by Dow Chemical Company, USA.

[0077] Hardness test: The Shore A measuring instrument was used, and measurements were taken according to GB / T 2411-2008. Measurement points were distributed between the outermost circles of the polishing pad, with an average of 8 points. The test result was taken as the average of the 8 measurement points, and the result was calculated to an accuracy of 0.1 ShA.

[0078] Compression rebound rate test: A digital thickness gauge was used, and measurements were taken according to JISK 6505-1995, the testing standards for artificial leather. Measurement points were distributed across three points on an equilateral triangle on the polishing pad. The product was placed under the fixed digital thickness gauge to measure the initial thickness, which was recorded as m0. An additional 250g pressure block and its support were then placed on top, and the thickness was measured after 5 minutes; this was recorded as m1. The pressure block was removed, and the product was allowed to regain its elasticity for 5 minutes. After another 5 minutes, the measuring rod was lowered again, and the thickness was measured after 30 minutes; this was recorded as m2.

[0079] Compression ratio and springback ratio are calculated using the following formulas: X1 = (m0 - m1) / m0 × 100%; X2 = (m2 - m1) / (m0 - m1) × 100%; Where: X1—polishing pad compression rate, %; X2—polishing pad rebound rate, %; m0—initial thickness of polishing pad, mm; m1—thickness of polishing pad after adding the fixing block, mm; m2—thickness of polishing pad after rebound, mm.

[0080] The test results are the average of the three measurement points, and the calculation is accurate to 0.1%.

[0081] Surface opening size analysis and testing: Uniformly sample the surfaces of polishing pad material A and polishing pad material B to determine four sampling points, such as... Figure 4 As shown, Figure 4 The numbers 1 through 4 represent the locations of the four sampling points. The distribution of the aperture size at each sampling potential was observed and analyzed using a scanning electron microscope.

[0082] Pore ​​and porosity testing: ImageJ software was used to test the porosity and porosity of the scanning electron microscope surface images. The measurement method was to use circumscribed ellipses (Major and Minor) and circumscribed rectangles (Width and Height).

[0083] Polishing test: Grinding rate tests conducted using a polishing machine testing equipment can evaluate the processing efficiency of this polishing pad on silicon wafer surface oxides, as well as the flatness of the polishing pad after processing. It can even reflect the performance of the polishing pad, such as its wear resistance and ability to absorb grinding fluids. Detailed test parameters are shown in Table 2 below.

[0084] Table 2. Parameters for Chemical Mechanical Polishing Rate Test Defect rate test: The defect rate of silicon wafer surfaces during chemical mechanical polishing (CMP) is measured using a CMP defect tester to evaluate the quality and efficiency of the polishing process. Defect rate testing is crucial for optimizing the polishing process, improving silicon wafer surface quality, and reducing the defect rate. A lower defect rate indicates a stronger ability of the polishing pad to remove defects from the silicon wafer surface, signifying better pad quality. The defect rate testing parameters and schedule are shown in Tables 3 and 4 below.

[0085] Table 3 Test Parameters for Chemical Mechanical Polishing Defects Table 4 Test Plan Test results: Table 5 Thickness of each layer of polishing pad Table 6 Physical properties of polishing pad materials A and B Figure 7 In the diagram, a) shows the microporous structure of polishing pad material A', b) shows the microporous structure of polishing pad material A, and c) shows the microporous structure of polishing pad material B. (Combined with...) Figure 7 As shown in Tables 5 and 6, the micropore structure of polishing pad material A' was coarse and distorted before the process improvement, but the micropore structure of polishing pad material A has been significantly optimized after the process improvement. Therefore, only the micropore morphology is compared, and no physical property analysis is performed on polishing pad material A'.

[0086] Hardness is the ability of a polishing pad to resist external forces, directly affecting the polishing effect of chemical mechanical polishing. Polishing pads with higher hardness have higher wear resistance and thermal stability, providing higher polishing efficiency and a longer service life; polishing pads with lower hardness have good elasticity and cause fewer surface defects to the polished object.

[0087] Depend on Figure 7 The thickness of each layer of the polishing pad was obtained by measuring and labeling the microporous structure, as shown in Table 5. The physical properties of the polishing pad were then analyzed, as shown in Table 6. The summary analysis is as follows: The hardness range of polishing pad material A is 87HA~91HA, and the hardness range of polishing pad material B is 88HA~94HA. The hardness of polishing pad material A and polishing pad material B are relatively close, indicating that polishing pad material A can replace imported polishing pad material B for polishing tasks with high surface requirements. The groove design is consistent with that of imported polishing pads, with no significant differences.

[0088] Regarding compressibility and resilience, polishing pad material A has a slightly lower compressibility than polishing pad material B, while its resilience is slightly higher. This is related to the fact that the polyurethane layer in polishing pad material A is thicker than that in polishing pad material B. Under the same pressure, this results in a relatively lower compressibility and a relatively higher resilience. Generally, polishing pads with low compressibility and high resilience can recover their shape more quickly upon pressure release, producing a better surface finish. This was also confirmed in subsequent polishing analyses regarding the reduction of defects during chemical mechanical polishing.

[0089] In summary, compared with polishing pad material A' before the process improvement, polishing pad material A after the process improvement has a significantly improved micropore structure that achieves the ideal teardrop shape, and the thickness of the polyurethane layer is increased, resulting in better performance than imported polishing pad material B.

[0090] Opening size analysis: like Figure 5As shown, the pore sizes at the four sampling points of polishing pad material A are concentrated in the range of 31μm to 40μm, accounting for 40%, 39%, 41% and 41% respectively, indicating that the pore sizes are relatively uniform.

[0091] like Figure 6 As shown, the pore sizes at sampling points 1 and 4 of polishing pad material B are mainly concentrated in the range of 31μm to 40μm, accounting for 40% and 37% respectively; the pore sizes at sampling points 2 and 3 are mainly concentrated in the range of 21μm to 30μm, accounting for 42% and 46% respectively. This indicates that polishing pad material B exhibits a tendency for pore sizes to increase or decrease in one direction, resulting in relatively poor uniformity in pore size distribution. Furthermore, combined with... Figure 5 and Figure 6 Overall, the statistical curves show that the overlap of the pore size curves of polishing pad material B is worse than that of polishing pad material A.

[0092] In summary, polishing pad material A exhibits superior uniformity in surface aperture size compared to polishing pad material B. This facilitates the flow and storage of the polishing slurry during chemical mechanical polishing (CMP), thereby improving the smoothness of the surface during the CMP process.

[0093] Pore ​​and porosity analysis: Figure 8 Figure a) is a scanning electron microscope (SEM) image of the surface of polishing pad material A; Figure b) is the corresponding ImageJ software analysis image of Figure a); Figure c) is a scanning electron microscope (SEM) image of the surface of polishing pad material B; and Figure d) is the corresponding ImageJ software analysis image of Figure c).

[0094] Depend on Figures 8-11 It is known that polishing pad material B has a higher porosity than polishing pad material A. The higher porosity of polishing pad material B, with its more numerous micropore structures, allows for better absorption and release of polishing fluid during the polishing process, helping to reduce surface friction and heat accumulation, making it suitable for objects requiring longer polishing times. In contrast, polishing pad material A has a relatively lower porosity and fewer micropore structures.

[0095] Chemical-mechanical polishing rate study: Related Figure 12 In the study, the Nu value of polishing pad material A was significantly lower than that of polishing pad material A' and polishing pad material B. The lower the Nu value, the smoother the surface. This is related to the fact that polishing pad material A has low compression ratio and high resilience physical properties, and that after the microporous structure is optimized through process improvement, it has a more uniform pore size, which increases the Nu value and achieves the purpose of smoothing.

[0096] Chemical mechanical polishing defect rate analysis: By testing for defects in chemical mechanical polishing (CMP), we compared polishing pad material A' before process improvement, polishing pad material A after process improvement, and imported polishing pad material B to analyze the impact of polishing pads on surface defects of silicon wafers when applied in CMP.

[0097] Figure 13 The silicon wafer undergoes a 60-second inspection according to the test plan, and defect maps are collected afterward. Figures a) to c) are defect maps corresponding to test condition 1 in Table 4; figures d) to f) are defect maps corresponding to test condition 2 in Table 4; and figures g) to i) are defect maps corresponding to test condition 3 in Table 4. The silicon wafer surface defect distribution map shows that one point represents one defect; more points indicate more defects. Figures a), d), and g) are defect maps after testing polishing pad material A'; figures b), e), and h) are defect maps after testing polishing pad material A; and figures c), f), and i) are defect maps after testing polishing pad material B.

[0098] Depend on Figure 13 It can be seen that the improved polishing pad material A achieves a higher surface defect removal rate on silicon wafers than the unimproved polishing pad material A', resulting in smaller surface defects after using polishing pad material A. However, it still lags behind the surface defect removal rate of silicon wafers polished with imported polishing pad material B. This may be because polishing pad material A has a relatively low porosity and fewer micropores. Therefore, its efficiency in absorbing and releasing polishing fluid during polishing is lower, leading to a relatively poorer defect removal effect.

[0099] In summary, the polishing pad material preparation method provided by this invention enables the polishing pad material to form a relatively stable and uniform microporous structure, thereby reducing surface defects on silicon wafers after polishing with soft polishing pad materials. This solves the technical problem of numerous surface defects on silicon wafers after polishing with existing polishing pad materials. The polishing pad material prepared by the method provided by this invention can be successfully applied to chemical mechanical polishing (CMP) processes.

[0100] The above description is merely a preferred embodiment of the present invention, and the specific embodiments described above are not intended to limit the present invention. Various modifications and variations can be made within the scope of the technical concept of the present invention. All refinements, modifications, or equivalent substitutions made by those skilled in the art based on the above description are within the scope of protection of the present invention.

Claims

1. A method for preparing a polishing pad material, characterized in that, Includes the following steps: The impregnated fabric is soaked in water to make the moisture content of the impregnated fabric between 25wt% and 28wt%, thus obtaining the bass. The polyurethane slurry is evenly coated on the surface of the base, and after solidification, an intermediate is obtained. The intermediate is washed with water, dried and surface treated to obtain polishing pad material; The concentration of the N,N-dimethylformamide solution used in the solidification molding process is 12wt% to 17wt%.

2. The method for preparing the polishing pad material according to claim 1, characterized in that, The coating thickness of the polyurethane slurry is 1.5 mm to 2.0 mm.

3. The method for preparing the polishing pad material according to claim 1, characterized in that, The solidification and molding process includes the following steps: The base coated with polyurethane slurry is immersed in N,N-dimethylformamide solution at a certain angle until it is completely submerged; Let α be the angle formed between the plane of the base coated with polyurethane slurry and the liquid surface of the N,N-dimethylformamide solution, and let the value of α be 25° to 35°.

4. The method for preparing the polishing pad material according to claim 1, characterized in that, The surface treatment includes sequentially performing a grinding process and a grooving process. The grinding process is used to expose the porous structure of the polishing pad material, and the grooving process is used to form a surface groove structure on the surface of the polishing pad material.

5. The method for preparing the polishing pad material according to claim 1, characterized in that, The water washing process includes: After rinsing intermittently 15 times, soak in water for 5 to 15 minutes, then rinse intermittently 15 times again.

6. A polishing pad material, characterized in that, The polishing pad material is prepared using the preparation method described in any one of claims 1 to 5.

7. The application of the polishing pad material of claim 6 in chemical mechanical polishing.

Citation Information

Patent Citations

  • Chemical mechanical polishing pad with uniform upright bubbles as well as preparation method and application of chemical mechanical polishing pad

    CN119609960A